Analisis Tes Bahasa Arab pada Kitab Durusullughah Juz II Karya KH Imam Zarkasyi dan KH Imam Subani - Bidari Bidari (Universitas Al-Amien Prenduan, 2018)
This article aims to analyze the Arabic test in the book Durusullughah juz II by KH Imam Zarkasyi and KH Imam Subani. This study uses a qualitative research approach with the type of library research (Library Research Method). This research method is carried out by descriptive-analytical method, which is a form of research that provides regular descriptions of the overall Arabic test to be studied. The results that the researchers obtained are: first, the forms of the test/practice are mostly in the form of memory questions (Objective Test) and mind questions (Subjective Test). Second, the advantages of the Arabic test in the book of Durusullughah juz II are very good to apply for beginners who want to learn Arabic, and the drawback is that it only uses some of the objective tests that already exist and are commonly used.